Experimental Study on the Performance of a Novel Unidirectional Explosive Element and an Explosive Logic Network - Fei Wang; Honghao Ma; Zhaowu Shen (Energies, 2022)
Considering the unsafety of the present blasting network used in the blasting mining of coalfield fires, a unidirectional explosive element (named explosive diode) is proposed according to explosive logic element principles. Through theoretical and experimental analysis, the internal structure and mechanism of the unidirectional transmission of the detonation signal were studied. For an explosive diode, the length of the quenching channel was defined to be the key parameter. The explosive diode was implemented in the traditional blasting network, obtaining an explosive logic network. To evaluate the safety and reliability of the explosive diode and explosive logic network, detonation propagation and explosion-proof experiments were conducted in the lab. The optimum length of the quenching channel to obtain unidirectional detonation transmission was established. The results showed that the explosive diode could reliably control the propagation direction of the detonation signal when the length of the quenching channel was between 15 mm and 25 mm. The explosive logic network achieved a reliable detonation propagation and was explosion-proof. In comparison with traditional networks, the explosive logic network showed increased safety and reliability as the number of subnets increased. This is a significant improvement to mining safety and demonstrates great promise for engineering applications.